TINGKAT KESIAPAN KOTA SURAKARTA TERHADAP DIMENSI MOBILITAS CERDAS (SMART MOBILITY) SEBAGAI BAGIAN DARI KONSEP KOTA CERDAS (SMART CITY) - Alfariani Pratiwi; Soedwiwahjono Soedwiwahjono; Ana Hardiana (Region : Jurnal Pembangunan Wilayah dan Perencanaan Partisipatif, 2015)
The city has a problem that often arises due to the construction of their own city. To prevent that, city management needs through a sustainable approach to the concept of planning. Now, the concept of smart city is developing, where several major cities in Indonesia have started implementing the concept. Surakarta be a pioneer in the use of technology of transportation commonly called Intelligent Transport Systems(ITS). Surakarta indicated to apply the concept of smart city. Together with Indosat, subsidiary of PT. Starone Partner Telecommunications (SMT) cooperate to apply the concept of smart city in Surakarta for example, e-transportation. E-transportation similar to the principle of smart mobility in the theory of smart city. Howerver not only the application of smart mobility technology, but also need to look at the aspects that provide comfort, security, and sustainability.This study wanted to see the level of readiness of Surakarta to smart mobility dimension as part of the smart city concept. The aspects of this research are local accessibility, international accessibility, multi-modal access, information and communication technology infrastructure supporting urban mobility, sustainable transport and safety. The analytical method used in this research is the analysis technique of scoring which  assess the readiness of each aspect and the overall readiness. The results showed that Surakarta belongs to the category ready but conditional on the application of smart mobility. This means Surakarta need to do several requirements either repair or procurement in some aspects. Aspects that have been prepared but has some requirements which need to be done are the aspect of local accessibility, international accessibility, multi-modal access, and information and communication technology infrastructure supporting urban mobility. Sustainable transport and safety aspects belong to the category not ready to support the implementation of smart mobility in Surakarta. Keywords: smart city, smart mobility, smart transportation